2020
DOI: 10.1073/pnas.2008025117
|View full text |Cite
|
Sign up to set email alerts
|

Rationing social contact during the COVID-19 pandemic: Transmission risk and social benefits of US locations

Abstract: To prevent the spread of coronavirus disease 2019 (COVID-19), some types of public spaces have been shut down while others remain open. These decisions constitute a judgment about the relative danger and benefits of those locations. Using mobility data from a large sample of smartphones, nationally representative consumer preference surveys, and economic statistics, we measure the relative transmission reduction benefit and social cost of closing 26 categories of US locations. Our categories include ty… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 4 publications
2
84
0
Order By: Relevance
“…Understanding how COVID-19 spreads is of paramount importance for managing the crisis and informing effective policies (27). The current work highlights the role of regional personality in a setting of high ecological validity by combining regional personality estimates derived from over 3.4 million participants in the US and Germany with official regional COVID-19 prevalence data and geo-tagged mobility data of approximately 29 million individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding how COVID-19 spreads is of paramount importance for managing the crisis and informing effective policies (27). The current work highlights the role of regional personality in a setting of high ecological validity by combining regional personality estimates derived from over 3.4 million participants in the US and Germany with official regional COVID-19 prevalence data and geo-tagged mobility data of approximately 29 million individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple research studies have found that population activities are important in predicting the growth of future cases. Benzell et al [44] identified risks associated with visits to venues at which people would be placed in proximity and showed that particularly high risk was associated with visits to restaurants, grocery stores, fast food establishments, cafes, and gyms. Also, Lai et al [45] found that there is high risk of small disease outbreaks within residential facilities for elderly, indicating that examining the number of visits to such facilities could be helpful in forecasting the growth of infection.…”
Section: A Feature Collectionmentioning
confidence: 99%
“…We consider visits to the following types of places in our model: amusement parks and arcades, colleges/universities/professional schools, living facilities for elderly, department stores, hospitals, merchandise stores/supercenters, grocery stores, and restaurants/eating places. As discussed in III-A, visits to grocery stores, restaurants/other eating places, living facilities for elderly, and hospitals could be particularly helpful in forecasting the growth of cases since these places could facilitate virus transmission [44] , is defined formally as [32]: where s i , s j represents the population activity intensity in cell i and j respectively and d ij represents the distance between the two cells. In our analysis, we define a cell to be a 4 km 2 area.…”
Section: B Population Activitiesmentioning
confidence: 99%
“…Our work is also related to a number of more empirical studies exploring the role of heterogeneity across sectors and across workers in the spreading of the infection and in designing efficient containment policies, such as Benzell et al (2020), Dingel and Neiman (2020), Kaplan et al (2020), Leibovici et al (2020), and Mongey et al (2020).…”
Section: Connection To Existing Literaturementioning
confidence: 99%